The city: Creative migration and the demise of small music venues - Bennett, Dawn (University of Regina, 2009)
The centrality of the arts to liveability and community wellbeing is clear, yet opacity surrounding the practice and conditions of creative artists presents a major impediment to effective policy and planning. Drawing findings from recent research, this paper considers arts practice in relation to the migration of creative artists from smaller cities and regions. The first phase of research gathered data from Western Australian creative artists living in Europe, the US and other Australian states. As expected, the dominance of major cities as centres of economic and cultural activity emerged as an obvious migration factor. More surprising was the strong link between local opportunities and the demise of small venues, which was most apparent in relation to live music. Smaller live music venues became, thus, the focus of the second research phase. The study found that creative artists most commonly migrate because of insufficient local opportunities and a desire to make new artistic connections. The results suggest that in order to fill large venues into the future, we must recognise the unique role played by small venues in developing audiences and artists, and fostering creativity and uniqueness.